The Influence of Auditor Competence and Moral Reasoning on Inspectorate Audit Quality with Organizational Commitment as A Moderating Variable - Dyna Febri Purwanti; Nur Handayani (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the influence of auditors' competence and moral reasoning on the quality of inspectorate audits, with organizational commitment as a moderating variable. The population in this study consists of all auditors from the Trenggalek Regency Government Inspectorate. This research employs a quantitative approach. The research sample includes all auditors of the Trenggalek Regency Government Inspectorate. According to the data obtained, there are 35 internal auditors in the inspectorate. The sampling method used is the saturated sample method. The saturated sample method is a sampling technique where all members of the population are used as samples. The data analysis technique in this study uses Moderated Regression Analysis (MRA). The results show that competence and moral reasoning have a significant positive effect on the quality of inspectorate audits. However, organizational commitment does not moderate the influence of competence on audit quality, nor does it moderate the influence of moral reasoning on audit quality.